2018
DOI: 10.1002/14651858.cd005461.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partograph use on outcomes for women in spontaneous labour at term and their babies

Abstract: Analysis 2.6. Comparison 2 Partograph with 2-hour action line versus partograph with 4-hour action line (studies carried out in a high-and low-resource settings), Outcome 6 Serious maternal morbidity or death.. .. .. .. Analysis 2.7. Comparison 2 Partograph with 2-hour action line versus partograph with 4-hour action line (studies carried out in a high-and low-resource settings), Outcome 7 Caesarean section (distress).. .. .. .. .. . Analysis 2.8. Comparison 2 Partograph with 2-hour action line versus partogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
104
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 43 publications
0
104
0
1
Order By: Relevance
“…The analysis found no association between availability of a partogram at the facility and cesarean, but did show that women who were referred during the course of labor had a higher odds of cesarean delivery. Use of the partogram has shown mixed effects in its ability to impact mode of delivery, suggesting that it may not be the ideal intervention to try and reduce cesarean delivery among women in Robson group 1 who are referred during labor . The WHO has asserted that assessment of cervical dilation over time is a poor predictor of severe adverse delivery outcomes, and that the validity of the alert line in the partogram, which is based on the “one‐centimeter‐per‐hour” rule, should be evaluated .…”
Section: Discussionmentioning
confidence: 99%
“…The analysis found no association between availability of a partogram at the facility and cesarean, but did show that women who were referred during the course of labor had a higher odds of cesarean delivery. Use of the partogram has shown mixed effects in its ability to impact mode of delivery, suggesting that it may not be the ideal intervention to try and reduce cesarean delivery among women in Robson group 1 who are referred during labor . The WHO has asserted that assessment of cervical dilation over time is a poor predictor of severe adverse delivery outcomes, and that the validity of the alert line in the partogram, which is based on the “one‐centimeter‐per‐hour” rule, should be evaluated .…”
Section: Discussionmentioning
confidence: 99%
“…India ranks very higher on the list of countries with high maternal mortality at 420 per 10, 000 live births. 1 In Punjab maternal mortality rate was 28%in 2012. 2 Maternal morbidity and mortality rate increases because of insufficient facilities in health care settings and inadequate knowledge and attitude of plotting the partograph.…”
Section: Introductionmentioning
confidence: 99%
“…Cochrane systematic review reported the study included one trial were compared a partograph with the latent phase (including early stages of labour) and one without the latent phase, the caesarean section and oxytocin augmentation rates were higher in the partograph with a latent phase. 17 There were no clear difference between groups for oxytocin augmentation, and Apgar score less than 7 at 5 minutes. Further, trial evidence was required to establish the efficacy of partograph use per se and its optimum design.…”
Section: Discussionmentioning
confidence: 80%